2009
DOI: 10.1007/s10571-009-9437-8
|View full text |Cite
|
Sign up to set email alerts
|

Stage Dependent Effects of Progesterone on Motoneurons and Glial Cells of Wobbler Mouse Spinal Cord Degeneration

Abstract: In the Wobbler mouse, a mutation in the Vps54 gene is accompanied by motoneuron degeneration and astrogliosis in the cervical spinal cord. Previous work has shown that these abnormalities are greatly attenuated by progesterone treatment of clinically afflicted Wobblers. However, whether progesterone is effective at all disease stages has not yet been tested. The present work used genotyped (wr/wr) Wobbler mice at three periods of the disease: early progressive (1-2 months), established (5-8 months) or late sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 83 publications
5
26
0
Order By: Relevance
“…In parallel with findings obtained in the spinal cord , the hippocampus of Wobbler mice developed an intense astrocytic reaction with a strong expression of GFAP. Astrogliosis may be a secondary response to neuronal degeneration, although it has also been considered a cell‐autonomous event of the Wobbler mouse and of the SOD1 transgenic mouse model .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In parallel with findings obtained in the spinal cord , the hippocampus of Wobbler mice developed an intense astrocytic reaction with a strong expression of GFAP. Astrogliosis may be a secondary response to neuronal degeneration, although it has also been considered a cell‐autonomous event of the Wobbler mouse and of the SOD1 transgenic mouse model .…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we investigated whether the effects of progesterone also take place in the hippocampus of this animal model. Mice in the symptomatic period of the disease were chosen because previous studies have demonstrated that this stage is more responsive to progesterone (23,33). First, our results show that the hippocampus was not spared from neurodegeneration.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Progesterone reduces reactive astrogliosis after traumatic brain injury and spinal cord lesions (Djebaili et al, 2005;Feeser and Loria, 2011;Garcia-Estrada et al, 1999Labombarda et al, 2011;Tang et al, 2013;VanLandingham et al, 2007) as well as in the hippocampus of Wobbler mice, an animal model of motor neuron degeneration (Meyer et al, 2013(Meyer et al, , 2010.…”
Section: Effects Of Progesteronementioning
confidence: 99%
“…erythropoietin and glucocorticoids) [71,72]. In addition, progesterone treatment has been shown to up-regulate GS in other tissues, such as the brain [73,74].…”
Section: Progesterone´s Effect On Retinal Glutamate Concentrationsmentioning
confidence: 99%